Penerapan Media Wattpad untuk Meningkatkan Keterampilan Menulis Teks Cerpen pada Siswa Kelas XI SMA Negeri 14 Gowa - Putri Awalia Rahmadhani; Sultan Sultan; Idawati Idawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to describe the application of Wattpad media in improving the ability to write short stories in grade XI students of SMA Negeri 14 Gowa. This study is a Classroom Action Research (CAR) with a mixed approach (qualitative and quantitative). The research subjects consisted of grade XI students of SMA Negeri 14 Gowa. The study was conducted in two action cycles that included planning, implementation, observation, and reflection. Data were collected through observation, testing, and documentation techniques, then analyzed qualitatively and quantitatively. The results of the study showed an increase in students' learning completeness in writing short stories through the application of Wattpad media. In cycle I, the learning completeness level reached 28.57%, while in cycle II it increased to 90.48% with a Minimum Completion Criteria (KKM) of 75. This increase was seen in the aspects of short story structure, creativity in story development, and better use of language. The application of Wattpad media also increased students' interest and motivation in writing, because it provided a more interactive and enjoyable learning experience. Thus, Wattpad is an effective medium for learning to write short stories and contributes to strengthening students' digital literacy.